EXAMINING MOTIVATION LEVELS OF FEMALE VOLLEYBALL PLAYERS AND COACH -PLAYER RELATIONSHIPS - Aksakal, Nalan; Sabırlı, Türkan Nihan; Kocaekşi, Serdar; Tokat, Ayça (International Journal of Research -GRANTHAALAYAH, 2018)
The aim of this study is to examine player-coach relationships and its relevance to motivational processes. The participants of the study were 93 players who played in the matches qualifying for Turkish 1st Women’s Volleyball League in 2018. The study used Player-Coach Relationship Inventory and Motivation in Sports Scale as the data collection instruments. The data obtained were analyzed by using SPSS 20 software, descriptive statistics and Pearson Correlation analysis. The findings of the study revealed no statistically meaningful relationship between player-coach relationship and external motivation and amotivation. However, there was a meaningful relationship between player-coach relationship and internal motivation (r=, 246). Similarly, a meaningful relationship was found between “the duration of player-coach relationship” and the sub dimensions of player-coach relationship, which are “commitment” (r=, 293), “closeness” (r=, 325) and “complementarity” (r=, 325). In short, it can be concluded that as the relationship between players and the coach improves, motivation increases, and as the duration of this relationship increases, player-coach relationship is affected positively.